Precision machining technology - Hoffman, Peter J.; Hopewell, Eric S.; Janes, Brian; Sharp, Kent M. (Delmar Cengage Learning, 2012)
Precision Machining Technology has been carefully written to align with the National Institute of Metalworking Skills (NIMS) Machining Level I Standard and to support achievement of NIMS credentials. This new text carries NIMS' exclusive endorsement and recommendation for use in NIMS-accredited Machining Level I Programs. It's the ideal way to introduce students to the excitement of today's machine tool industry and provide a solid understanding of fundamental and intermediate machining skills needed for successful 21st Century careers. With an emphasis on safety throughout, PRECISION MACHINING TECHNOLOGY offers a fresh view of the role of modern machining in today's economic environment. The text covers such topics as the basics of hand tools, job planning, benchwork, layout operations, drill press, milling and grinding processes, and CNC. The companion Workbook/Shop Manual contains helpful review material to ensure that readers have mastered key concepts and provides guided practice operations and projects on a wide range of machine tools that will enhance their NIMS credentialing success. - Publisher.